Jinmaitong Alleviates Diabetic Neuropathic Pain Through Modulation of NLRP3 Inflammasome and Gasdermin D in Dorsal Root Ganglia of Diabetic Rats - Sun, Qing; Zhang, Rui; Xue, Xiaowei; Wu, Qunli; Yang, Dan; Wang, Chao; Yan, Bin; Liang, Xiaochun (Frontiers in Pharmacology, 2021)
Jinmaitong (JMT) is a compound prescription of traditional Chinese medicine that has been used to treat diabetic neuropathic pain (DNP) for many years. Here, we investigated the effects of JMT on the activation of NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome and pyroptosis in dorsal root ganglia (DRG) of diabetic rats. Streptozotocin (STZ)-induced diabetic rats were gavaged with JMT (0.876 g/kg/d) or alpha-lipoic acid (ALA, positive control, 100 mg/kg/d) for 12 weeks. Distilled water was administered as a vehicle control to both diabetic and non-affected control rats. Blood glucose levels and body weights were measured. Behavioral changes were tested with mechanical withdrawal threshold (MWT) and tail-flick latency (TFL) tests. Morphological injury associated with DRG were observed with hematoxylin and eosin (H&E) and Nissl’s staining. mRNA and protein levels of NLRP3 inflammasome components (NLRP3, ASC, caspase-1), downstream IL-1β and gasdermin D (GSDMD) were evaluated by immunohistochemistry, quantitative real time-PCR and western blot. The results showed that JMT had no effect on blood glucose levels and body weights, but significantly improved MWT and TFL behavior in diabetic rats, and improved morphological damage in the DRG tissues. Importantly, JMT decreased the mRNA and protein levels of components of NLRP3 inflammasome, including NLRP3, ASC and caspase-1. JMT also down-regulated the expression of IL-1β and GSDMD in the DRG of DNP rats. In addition, ALA treatment did not perform better than JMT. In conclusion, JMT effectively relieved DNP by inhibiting NLRP3 inflammasome activation and pyroptosis, providing new evidence supporting JMT as an alternative treatment for DNP.